A scientometric review of digital competency among educators during the past 10 years - Mohd Rosli, Nur Dania; Md Khambari, Mas Nida; Wong, Su Luan; Zakaria, Noor Syamilah; Abdullah, Kamilah; Hamzah, Siti Raba’Ah; Moses, Priscilla; Abdrahim, Nur Aira (Institute of Advanced Engineering and Science, 2025)
This study interest in examining the digital competency of educators in educational institutions. Digital competency is of utmost importance in today’s technologically advanced society due to the pervasiveness of technology not only in the classroom but also in our daily lives. This study analyzed 1,189 journal articles from the Scopus database based on bibliographic coupling and co-word analysis using bibliometric analysis. The period of time covered by the study was from 2013 to 2022. Findings indicated that there has been an increase in the number of studies concentrating on digital competency among educators, with this increase becoming more pronounced during the COVID-19 outbreak. Significant themes emerged in relation to educators’ digital competence, particularly concerning the significance and global impact of these characteristics. Bibliographic coupling yields five clusters for current research, whereas co-word analysis yields four clusters for predicting future trends. As a result, some suggestions were made with the intention of contributing to the relevant research community based on study’s findings.